The impact of BRICS expansion on rivalries in West Asia and North Africa - Imad Mansour; Abdelhadi Baiche (Asian Review of Political Economy)
Abstract The BRICS + collective (Brazil, Russia, India, China, and South Africa, with the + to denote the expansion in membership) claims to represent Global South (GS) interests. Core among these interests is to ameliorate global structural exchange inequalities through reforms to global governance architectures and encouraging collaboration among members. Reforms and collaborative work aim at improving economic conditions in the GS, which is a long-standing local demand. At the same time, GS regions suffer from rivalries among its constitutive members states. Regional rivalries contribute to worsening economic conditions by discouraging investments, limiting the utilization of regional complementarities, and channeling money towards arms build-up. This article argues that given BRICS + emphasis on fostering economic reforms and members’ interdependence, membership in this collective incentivizes rivals to de-escalate so that they can capture benefits in the service of their national interests. BRICS + members observe the behavior of rivals since it is in the interest of the collective to uphold its credibility and fulfil its promises. De-escalation occurs as states prioritize cooperation over conflict, benefiting from economic opportunities and shared platforms for exchanges and dialogue. The article examines the potential of BRICS + to create conditions conducive to rivalry de-escalation in West Asia and the Maghreb (WAM). The organizational structure of BRICS + as a flexible, Global South-oriented coalition makes it attractive to states with existing tensions, encouraging pragmatic steps toward de-escalation. But BRICS + itself accepts membership based on existing members unanimously accepting potential newcomers; these newcomers are primarily evaluated on the premise of their positive contributions to the goals of the collective and are (apparently) shunned if their membership brings divisions and rivalry to within the collective. We select for our analysis three case studies which vary in their demonstration of the effects of BRICS + membership/promise of membership on the rivalry. The cases offer insights into how the BRICS + collective has utilized the membership process to promote de-escalation—instrumentalizing it as a preliminary condition for joining. Accordingly, the Morocco-Algeria rivalry provides the strongest evidence of BRICS + activism, the Egypt-Ethiopia rivalry yields mixed results, and the Saudi Arabia-Iran rivalry presents the least robust evidence of instrumentalization (relative to other cases). This categorization is based on how strongly each case supports our study’s claims. Curiously, we find that the impact of these processes on security dynamics in the regional order varied – the outcome is reversed. This means that BRICS + succeeded in leveraging membership to de-escalate the Saudi Arabia-Iran rivalry and, to a lesser extent, achieved similar results with Egypt and Ethiopia. In contrast, the Morocco-Algeria rivalry demonstrates the limits to which BRICS + was able to instrumentalize membership as a tool for de-escalation and highlights the subsequent lack of contribution to regional security, which the collective could not achieve despite its potential to do so.